2010
DOI: 10.1097/tp.0b013e3181cbac02
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Histology: Lowering Human Leukocyte Antigen Antibody to Improve Renal Allograft Survival in Acute Rejection

Abstract: In conclusion, failure to significantly reduce antibody levels and prevent new formation was strongly predictive of allograft loss. This observation suggests that the therapeutic intervention that reduces antibody production may prolong graft survival in transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 23 publications
2
35
0
Order By: Relevance
“…It has been shown that a fast reduction of DSAs results in better graft survival [60,61]. The most important trial studying the treatment of CAMR in children was carried out by Toenshoff and Billing.…”
Section: Chronic Antibody-mediated Rejection (Camr)mentioning
confidence: 99%
“…It has been shown that a fast reduction of DSAs results in better graft survival [60,61]. The most important trial studying the treatment of CAMR in children was carried out by Toenshoff and Billing.…”
Section: Chronic Antibody-mediated Rejection (Camr)mentioning
confidence: 99%
“…Late AMR is associated with chronic pathology and worse dysfunction at the time of diagnosis, mixed cellular and humoral features, and subsequently, lower treatment response rates, [132][133][134] but it is notable that DSA MFI does not reliably further stratify those individuals who will respond to treatment from those who will do not. 133 Indeed, in one study, those who responded to treatment had higher antibody level as estimated by MFI than nonresponders.…”
Section: Dndsa and Features Of Amrmentioning
confidence: 99%
“…133 Indeed, in one study, those who responded to treatment had higher antibody level as estimated by MFI than nonresponders. 135 Others that do report an association of MFI and treatment response 134,136 note wide overlap in MFI ranges between response groups with no clear discriminating thresholds.…”
Section: Dndsa and Features Of Amrmentioning
confidence: 99%
See 1 more Smart Citation
“…Among kidney transplant recipients with biopsyproven antibody-mediated rejection, those who responded to treatment with T cell depletion with or without plasmapheresis had significantly better longterm graft survival than nonresponders. 57 Interestingly, two-thirds of the responders did not receive any therapy aimed directly at reducing circulating antibodies, such as plasmapheresis, and this highlights the role of cellular immunity underlying the clinical diagnosis of antibody-mediated rejection. Similarly, non-HLA IgG autoantibodies, which are detected in liver transplant recipients at a much higher rate in comparison with the general population, respond to steroids or T cell-targeting therapy.…”
Section: Possible Mechanism Of Donor-specific Human Leukocyte Antigenmentioning
confidence: 99%